Towards Better Expenditure Quality : Guatemala Public Expenditure Review - World Bank (Washington, DC, 2013)
Guatemala has made tremendous strides in moving toward democracy and building institutions after a prolonged civil war, much remains to be done in generating the foundations for strong broad-based economic growth. As Guatemala enters its fifth presidential cycle since the 1996 Peace Accords, the newly elected administration faces tremendous economic challenges. Efforts during the previous administration to directly address poverty and improve education and health outcomes, particularly in the indigenous and rural areas, were intense, with tentative signs of success. The signing of the Peace Accords in 1996, following a protracted negotiations process, marked a turning point in Guatemala's development path. Three cross-cutting themes were emphasized through the Accords: 1) the rights of indigenous communities; 2) commitments regarding the rights and position of women, and 3) a strengthening of social participation. However, Guatemala's institutional environment continues to complicate the cooperation of political actors over time and thus the inter-temporal bargains required to agree upon and sustain structural reforms. Over the past two decades, economic growth has been relatively stable but weak. Since 1990, real Gross Domestic Product (GDP) growth per capita in Guatemala has averaged about 1.2 percent, about three-quarters of a percentage point less than the rest of Latin America and the Caribbean and significantly less than other middle-income countries. Financial sector legal and regulatory reforms implemented since 2000 have improved banks' solvency and resilience to market volatility, but lack of access to finance remains a major issue for the financial sector. To accelerate broad-based growth, Guatemala will need to improve the investment climate for business, increase educational attainment and make progress on governance, transparency and security.